Checklist of earthworms (Oligochaeta: Lumbricidae) from Montenegro: Diversity and biogeographical review - Stojanović, Mirjana; Milutinović, Tanja (Zootaxa, 2013)
A checklist of the lumbricid earthworms in Montenegro is presented. Comprehensive information on the distribution and habitats of all earthworms is given in order to establish the definitive list of known taxa from Montenegro. The complete list of earthworm taxa of Montenegro comprises 40 species and subspecies, belonging to 12 genera of the family Lumbricidae. The list underlines the diversity of earthworms and provides a general overview of their distribution and zoogeographical type. Our study shows that the degree of endemism is comparatively high, exceeding 20%. Summing up the endemics and the Balkanic species, 42.5% of the total lumbricid fauna shows an autochthonous character.